64 755
Assignments Done
99,3%
Successfully Done
In September 2018

Answer to Question #19966 in Algebra for prince sharma

Question #19966
Proof that x^0=1
Expert's answer
We know, that:
(x^a)*(x^b) = x^(a+b)
1*x^b = x^b
So,
(x^0)*x^b = x^b => x^0=1

Need a fast expert's response?

Submit order

and get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

Comments

No comments. Be first!

Leave a comment

Ask Your question

Submit
Privacy policy Terms and Conditions